ANALISIS YURIDIS TERHADAP LELANG BARANG JAMINAN YANG HAK TANGGUNGANNYA BELUM TERPASANG (STUDI PADA PT. BANK MANDIRI (PERSERO) TBK) - DEVI MUTIA MASTURA (PREMISE LAW JURNAL, 2017)
A credit contract is an agreement between Bank and debtor which binds them in contract. It is closely related to credit guarantee as a part of an agreement between both of them. It can be a plot of land as hypothecation. The result of the research showed that the process of burdening hypothecation at PT. Bank Mandiri (Persero) Tbk, Medan, was carried out in two stages: a) giving hypothecation done before PPAT (Official Empowered to Draw up Land Deeds) appointed by PT Bank Mandiri (Persero) Tbk, Medan, and b) registration of hypothecation carried out in the Land Office. The policy made by PT. Bank Mandiri (Persero) Tbk, Medan, to settle the problem of collateral with no hypothecation which will be auctioned by registering it, paying off the credit, and selling the collateral. When this effort fails due to debtor’s bad faith, the case will be brought to the Court.Keywords: Hypothecation, Auction, Collateral with No Hypothecation